Media Sosial dan Komunikasi Politik: Kajian Sistematik Efek Pesan Politik Pada Pemilu - Sari, Sandra Buana; Irwanti, Marlinda (Magister of Communication Science, Sahid University Jakarta., 2025)
This study examines the effects of social media messages on political campaign outcomes in the context of national elections and local elections (pilkada). Using a Systematic Literature Review (SLR) approach, this research identifies patterns, trends, and findings from previous studies. The results indicate that social media messages influence voters on three dimensions: cognitive (enhancing knowledge), affective (emotional engagement), and behavioural (encouraging actions). Social media provides significant opportunities to strengthen candidate images, raise political awareness, and increase voter participation. However, misinformation and fake news pose substantial challenges, undermining campaign integrity and public trust. These findings highlight the dual role of social media in political communication: as an effective tool for voter engagement and as a medium susceptible to spreading false information. This study recommends ethical and data-driven communication strategies to maximize the positive impacts of social media in political campaigns.